Innovative IaaS Management System for Sensor Devices and IT Resources - Hitomi Takahashi; Takayuki Kushida (International Journal of Distributed Sensor Networks)
Current sensor networks have various types of sensor devices with different network protocols. Most users directly connect to the sensor devices with limited IT capabilities. This ad hoc method of using sensor networks has many limitations. First, multiple users cannot share a sensor device at the same time. Second, users cannot deploy applications for various sensor devices easily and quickly. To solve these problems, we propose the innovative IaaS management system for sensor devices in which the sensor devices are managed as one of the IT resources in the same way as CPUs, storage, and networks in the cloud computing. We call this cloud environment “Sensor Cloud (SC).” SC allows multiple users to share the sensor devices instead of the sensor data. SC adapts three cloud features for sensor devices, “virtualization,” “automation,” and “standardization.” We implemented SC and deployed it on actual server environments hosting the existing cloud software. The evaluation results of SC show that the transmission delay for sensor data between the sensor devices and the users in SC was decreased by up to 81% compared to a typical cloud computing implementation.